Propuesta de mejora a los procesos de registro asistencia estudiante y asignación carga horaria de la Escuela Superior Politécnica Agropecuaria de Manabí - Solórzano Bermeo, Vicenta Marilyn (2017)
This research was conducted with the aim of proposing improvements to processes of record attendance student and allocation of load time of the school Superior Polytechnic agricultural Manabí Manuel Felix Lopez, so that it contributes to the efficiency of the same. For this purpose applied techniques as: observation, interview and analysis of value added, which helped to graphically represent processes, showing clear and easily the same path. Also determined the activities that add and non-value added processes support student registration and assignment of hourly load of the MFL spam in the different departments involved, providing the necessary guidelines for the elaboration of a proposal for improvement, focused on the optimization of resources and activities, while socialization help to all those involved in the process know the necessary corrective actions to reaches the effectiveness and satisfaction of the internal and external users. Therefore this research was essential to implement management processes in the MFL ESPAM, pushing the processes involved to improve, which is achieved by designing, control and continuously improve the processes, avoiding the wastage of resources and increasing the productivity, efficiency, and adding value to the customer and the institution.